Derivasi Kata Menangis dan Ragam Maknanya dalam Al-Qur’an (Analisis Semantik) - Sri Elsa Fatima Madaris (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2022)
This research aims to determine the derivation of words crying and their various meanings based on semantic analysis. This type of research is qualitative research using library research methods (literature review), namely data collection and data analysis in the form of journals, articles, and theses. The results of this study indicate that the word cry in Arabic has two terms, namely Baka> and Dam’, each of the two words has a different derivation and meaning. The word Baka> is mentioned 7 times in various grammatical forms, while the word Dam’ is mentioned twice. This brings up different meanings of the word, between the meaning of the word cry and its derivation in the Qur’an, namely crying with the word Baka> which means crying because of lamentation, crying simultaneously with tears, wishing for a voice accompanied by crying, Baka> also divided into two, namely crying that is allowed and crying that is prohibited. Meanwhile, the word Dam’ has a meaning that is the name of something that flows from the eye. According to Imam Ibn al-Qayyim al-Jauzi, the types of cries are: (1) cries of affection; (2) crying out of fear; (3) cries of love and longing; (4) cries of happiness and joy; (5) cry of worry; (6) crying sadness; (7) crying weakness; (8) cry of hypocrisy; (9) rental cries; and (10) cry of agreement.